Aksesibilitas Transportasi Publik Bagi Penyandang Disabilitas Pengguna Light Rail Transit Sumatera Selatan - Tahta, M. Hafidz; Nasyaya, Annada (Jurusan Administrasi Publik, FISIP, Universitas Sriwijaya, 2023)
This study aims to provision of accessibility to public transportation for people with disabilities is still a problem. This is because there are still many complaints coming from people with disabilities regarding the provision of accessibility on public transportation, which is still not good. As one of the public transportations in Palembang City, the South Sumatra Light Rail Transit needs to provide accessibility for people with disabilities. This is so that people with disabilities can use the South Sumatra Light Rail Transit transportation easily and comfortably. This type of research uses descriptive and qualitative research methods. Researchers conducted interviews with people with disabilities who use the LRT in South Sumatra and LRT officers in South Sumatra to find out how accessible it is for people with disabilities who use the LRT in South Sumatra. In this study, researchers used the Atlas.ti tool to assist in analyzing the data. In this study, it is known that accessibility for people with disabilities has been carried out well. This can be seen from the opinions of people with disabilities who are satisfied with the facilities and services provided when using the South Sumatra LRT public transportation service. Even so, there are still some shortcomings that must be corrected and resolved.